We’re exhausting ourselves, let’s get busy instead: a comment on the contributions by Jakob v.H. Holtermann, Mordechai Kremnitzer and Daniela Demko - Drumbl, Mark A. (Why punish perpetrators of mass atrocities?, 2021)
In his comment on the contributions by Holtermann, Demko and Kremnitzer, Mark Drumbl engages with their respective pleas for a predominance of deterrence, expressivism and retribution. In reference to Kremnitzer’s contribution on retribution, he doubts that ‘victimizers-victims’ deserve punishment. They might deserve something else, but something that is not delivered in a criminal courtroom. While he is sympathetic to the expressivist theory and the communicative function of punishment, as developed by Demko, he doubts that a court room is the best place to host those conversations. He worries that the medium – the court – becomes the message. Similarly, he doubts that the courtroom is the best place to tell the truth. The criminal trial illuminates selectively, not comprehensively. It communicates an incomplete truth that does not shed light on the bystanders, and complicity, side-standers. Finally, with regard to Holtermann, Drumbl – as one of the critics of deterrence that Holtermann criticizes – remains unconvinced that international punishment has a deterrent effect. For him, deterrence can at best be believed through a combination of anecdote, superimposition, and faith.